2017
DOI: 10.1021/jacs.7b09124
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric Synthesis of Quaternary Barbituric Acids

Abstract: The catalytic asymmetric α-functionalization of prochiral barbituric acids, a subtype of pseudosymmetric 1,3-diamides, to yield the corresponding 5,5-disubstituted (quaternary) derivatives remains essentially unsolved. In this study 2-alkylthio-4,6-dioxopirimidines are designed as key 1,3-diamide surrogates that perform exceedingly in amine-squaramide catalyzed C-C bond forming reactions with vinyl ketones or Morita-Baylis-Hillmann-type allyl bromides as electrophiles. Mild acid hydrolysis of adducts affords b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…In addition, catalysts III and VI were also prepared according to the literature procedure. 15 Catalyst IV (CAS no: 1211565-08-0) was purchased from Sigma-Aldrich and Daicel Chiral Technologies. Catalyst VI was prepared from (+)-quinidine (CAS number 56-54-2, purchased from Alfa Aesar).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, catalysts III and VI were also prepared according to the literature procedure. 15 Catalyst IV (CAS no: 1211565-08-0) was purchased from Sigma-Aldrich and Daicel Chiral Technologies. Catalyst VI was prepared from (+)-quinidine (CAS number 56-54-2, purchased from Alfa Aesar).…”
Section: Methodsmentioning
confidence: 99%
“…That is noteworthy as this requires the chiral discrimination between an NMe and NH amide moieties of the pro-nucleophilic partner 20. Recently, Palomo and co-workers tackled the enantioselective alkylation reaction of non-symmetrical barbituric acid derivatives making use of an organocatalytic strategy (Scheme 5) [31]. After the observation of very moderate ees obtained using (thio)barbituric acid nucleophiles, this research established that 2-alkylthio-4,6-dioxopyrimides 25 were competent barbituric acid surrogates for the conjugate addition reaction to vinyl aryl ketones 26.…”
mentioning
confidence: 99%
“…Notwithstanding this major achievement in this field of research, the Michael reaction could not be extrapolated to less reactive acrylate derivatives, and the moderately sterically hindered acrolein led to a modest ee of 48% [31]. Nevertheless, this group showed that enone 30 (Scheme 6), a precursor of acrylates or acrolein after oxidative cleavage sequences, was able to undergo the stereoselective conjugate addition of 25 under rather similar organocatalytic conditions to give barbituric acid products 31 with ees between 81% and 94%, after an acidic hydrolysis of the 2-benzylthioether moiety.…”
mentioning
confidence: 99%
See 2 more Smart Citations